Pointwise error estimates in localization microscopy - Martin Lindén (Nature Portfolio, 2017)
Super-resolution localization microscopy produces biophysical information in the form of estimated positions of single molecules. Here, Lindénet al. estimate the uncertainty of single localizations, and show that this additional information can improve data analysis and localization precision.